Liquidity Management and Financial Performance of SACCOs in Bushenyi District - Benjamin Musiita; Ben Boyi; Thomas Kisaalita; Wycliffee Mutungi; Robert Mbabazize (Journal of Economics and Behavioral Studies, 2023)
The main objective of this paper is to examine the association between elements of liquidity management and the financial performance of SACCOs in Bushenyi District. This research was conducted through a cross-sectional survey involving a sample of 72 Savings and Credit Cooperative Societies (SACCOs) located in the Bushenyi District. A sample of 61 SACCOs operating in Bushenyi was determined using Krejcie and Morgan's Table, with accountants, managers, and credit officers serving as the units of analysis, resulting in a total population of 183 respondents. The research instrument's validity was assessed using the content validity index, and its reliability was evaluated through Cronbach's alpha coefficient, a measure of the consistency in obtaining similar results from the same respondents when administering the instrument at different times. In accordance with the research objectives, inferential statistics, specifically correlation and regression analyses, were conducted. The findings reveal a statistically significant positive correlation between cash ratios, liquidity ratios and financial performance. Lastly, the research outcomes demonstrate a statistically significant positive relationship between the comprehensive liquidity management elements and financial performance. This suggests that any favorable change in the management of liquidity within SACCOs is associated with a positive change in financial performance. Therefore, enhancing liquidity management can aid in maximizing the use of cash on hand, while efficient cash budgeting can guarantee good planning and resource allocation. Due to their weakly positive associations with liquidity management, debtor management, as well as bank reconciliation statements, must also be considered; this will improve the financial performance of SACCOs.